Edukacija nadarjenih učencev v luči raziskav pedagoške psihologije - Ferbežer, Ivan (Psihološka obzorja (Ljubljana), 2006)
The paper tries to find connections between modern mainstreams of research in educational psychology and the education of gifted students. Contemporary fields of cognition, learning and development are getting more and more important in the process of establishing efficient teaching and learning environment for gifted students. Concerning the theory of teaching and learning the paper emphasizes three main components: theory of experts' experiences, theory of recognition and theory of educational intervention. On this basis principles of stimulated, proactive learning environment for efficient education of gifted students are then formed.
Keywords: Pedagoška psihologija; Nadarjeni otroci; education; izobraževanje; nadarjeni učenci; learning; učenje